PERSONALITY PHENOMENON IN PSYCHOLOGY (Journal of Universal Science Research, 2023)
One of the unique aspects of human nature is its aspect related to the life of society, which is an aspect that requires the study of the problem of the individual. The study of various aspects of human existence has a long historical tradition. This multidimensionality, versatility and diversity in the aspect of a person's personality determine his uniqueness.